Transcrestal guided sinus lift without grafting materials: a 36 months clinical prospective study - SPINELLI, D. (Oral Implantol (Rome), 2016)
PURPOSE: This study describes the ability to perform a technique for bone regeneration in maxillary posterior deficit (TGSL) without the use of bone grafting materials using a highly minimally invasive protocol. MATERIALS AND METHODS: Sixty six implants have been inserted in the sinus floor of a total of 39 patients through the transcrestal guided sinus lift technique (TGSL). All patients have been followed for at least three years in function. The drilling protocol was adapted on the basis of bone density of each implant site to achieve a torque between 45 and 55 Ncm. Healing titanium abutments tightened to 35 Ncm have been used. A CAD/CAM metal ceramics final prosthetic restoration has been generated a six months after the tissues healing and the provisional functionalization of the occlusion. Survival rate of implants and prostheses, biological and biomechanical complications, changes in marginal bone levels, and total height of alveolar crest bone before and after surgery have been evaluate and measured by the results obtained in this prospective study. It was also measured the periodontal parameters as well as levels of perception of pain by the patient during the entire recovery period. RESULTS: The result of the data of follow-up was 41.96 (24 to 36) months. Cumulative implant survival was 98.53% at 3 years. There were no biological and mechanical complications and there were no prosthetic failures during the whole period of follow-up. The Marginal Bone Loss (MBL) average during the first year of operation was from 0.33 to 0.36 mm, while the 3-year follow-up, the MBL average was 0.51 to 0.29 mm. The average of residual bone height of alveolar ridge before treatment was 6.7 to 1.6 mm (range 5.1 to 9.2 mm), while the average bone height was gained 6,4 – 1.6 mm (range 3.2 to 8.1 mm). All patients reported lower pain levels and found to have normal periodontal parameters. CONCLUSIONS: This study suggests that the use of guided surgery to perform transcrestal maxillary sinus lift to increase the sub-antral crestal height is a minimally invasive technique of success for the short and medium-term of follow-up, thus avoiding the extended treatment time and reducing the morbidity associated with the lifting of the floor of the maxillary sinus with traditional technique using bone grafting materials. Furthermore, this protocol without the use of graft materials does not vary the final outcome that have demonstrated the presence of newly formed bone around implants offering always predictable results, and giving a further reduction in the costs of the procedure rehabilitation.